Perica, Vjekoslav, “ The Sanctification of Enmity. Churches and Construction of Founding Myths of Serbia and Croatia.” - Goldstein, Ivo (Array, 2005)
Article compares parallel processes of construction of nationalist myths in Croatia and Serbia during the socialist era and beyond emphasizing roles of religious organizations.